Analysis of infrasound data of the meteorite of Aguas Zarcas of San Carlos, Costa Rica, april 23, 2019 - Quintero-Quintero, Ronnie (2019)
On April 23, 2019, at 21:07:22 (Costa Rica time), the cameras of the Vulcanological and Seismological Observatory of Costa Rica of the National University, located in the Poas and Turrialba volcanoes, captured a resplendence in the atmosphere. That luminosity corresponded to a meteorite that fell in the district of Agua Zarcas in San Carlos. This was also registered in the infrasound arrangement located in the Turrialba volcano between 03:12:19 and 03:12:37, UTC (local time+ 6hrs) with a duration of 18 seconds. At 03:12:19 the signal showed a backazimut of 302.4°N, apparent velocity of 347,0 m/s and a pressure of 0,13 Pascal (Pa), also showed a greater amplitude at 03:12:23 with 0,23 Pa, backazimut of 302,3° and apparent velocity of 352 m/s. The data with high correlation (> 0,6) indicated that this meteorite generated an infrasonic wave with an apparent velocity of 359 m/s, backazimut of 302,4°N, an average frequency of 2,864 ± 1,582 Hz and a maximum amplitude of 0.23 Pa. This meteorite was considerated small with an estimated energy of 2.74 X 1010 Joules. It was seen from towns such as Cartago, Turrialba, Puntarenas, Liberia, Escazu, Fraijanes, San Ramon, Venice, Ciudad Quesada and Aguas Zarcas de San Carlos.